INTEGRASI HRIS DAN SOCIETY 5.0 DALAM SISTEM EVALUASI KINERJA PEGAWAI: STUDI PADA PENGADILAN TATA USAHA NEGARA BANJARMASIN - Akhmad Fauzanor; Zakky Zamrudi; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the performance evaluation system at the Administrative Court of Banjarmasin (PTUN Banjarmasin) and formulate an evaluation model that integrates the Human Resource Information System (HRIS) with Society 5.0 principles. A qualitative case study approach was employed through in-depth interviews, limited participant observation, and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that the existing evaluation system remains administrative and does not adequately represent employees' digital workload. The integration of HRIS and Society 5.0 enhances objectivity, accuracy, and transparency by enabling real-time digital performance tracking and incorporating indicators such as technological adaptability, collaboration, and problem-solving capabilities. This model can motivate staff, develop their competencies, and support the Smart Court transformation, inspiring confidence in the system's positive impact.